2013
DOI: 10.1615/atomizspr.2013007155
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Rayleigh-Plateau Instability Limit Using Thermocavitation Within a Droplet

Abstract: We report on the generation of liquid columns that extend far beyond the traditional Rayleigh-Plateau instability onset. The columns are driven by the acoustic pressure wave emitted after bubble collapse. A high-speed video imaging device, which records images at a rate of up to 10 5 fps, was employed to follow their dynamics. These bubbles, commonly termed thermocavitation bubbles, are generated by focusing a midpower (275 mW) continuous wavelength laser into a highly absorbing liquid droplet. A simple model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…To provide a qualitative demonstration of the efficacy of optical clearing in skin treated with the optimal PG perfusion enhancement protocol, we utilized a thermocavitation technique we reported previously . Briefly, treated ex vivo porcine skin was placed on the outer face of a quartz cuvette containing saturated aqueous copper nitrate solution (CuNO 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…To provide a qualitative demonstration of the efficacy of optical clearing in skin treated with the optimal PG perfusion enhancement protocol, we utilized a thermocavitation technique we reported previously . Briefly, treated ex vivo porcine skin was placed on the outer face of a quartz cuvette containing saturated aqueous copper nitrate solution (CuNO 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…CW thermocavitation has been observed to produce bubbles that collapse in a toroidal shape when formed near a solid boundary [16]. When a bubble collapses near a heated solid boundary, the microstream jet will be comprised of colder liquid from outside the heated layer near the boundary.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a continuous wave (CW) laser focused into a hemispherical droplet of highly absorbing liquid has proven to be an alternative technique to produce liquid jets, eliminating the use of nozzles, capillaries, or microcavities. The liquid jets produced by this method are driven by an acoustic shock wave (ASW) emitted at the collapse of a vapor bubble within the droplet contrary to short-pulsed laser-induced cavitation whose dynamic is determined by the bubble [32]. It was shown that the bubble produced by CW lasers is always in contact with the substrate (glass) due to the large optical absorption of the overlaying droplet.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the bubble produced by CW lasers is always in contact with the substrate (glass) due to the large optical absorption of the overlaying droplet. The propagation of the ASW was simulated using a ray tracing model as point source originated at the substrate [32]. The simulation shows that the ASW is reflected by the droplet's surface due to an acoustic impedance mismatch (R 99.99) between the solution and air; i.e., the interface acts as a perfect mirror, reflecting the ASW toward the point where it was emitted.…”
Section: Introductionmentioning
confidence: 99%